Estudo da audição e incômodo auditivo em trabalhadores do setor canavieiro expostos a ruído e produtos químicos - Nelli, Maíra Pietraroia (2015)
Continuous noise exposure can cause auditory and non-auditory effects, such as: annoyance, irritability, stress, fatigue, headaches, and lack of attention, among others. Besides noise, several chemicals in the workplace may cause deleterious health effects. Objective: Study auditory effects and noise annoyance among sugarcane industry workers exposed to noise and chemicals. Method: The sample consisted of 120 male workers of sugarcane industry divided into four groups: Control Group (C), 30 workers non exposed; Chemical Group (Q), 30 workers exposed to herbicide, but not to noise; Noise Group (R ), 30 workers exposed to noise, but not to chemicals, and Noise and Chemical Group (RQ), 30 workers exposed to noise and chemicals. The procedures included pure tone audiometry, interview and a questionnaire (based on Ferreira, 2013). The statistical analysis was performed in several steps. For selected variable, the chi-square test of homogeneity was applied and the level of significance adopted was 5% in each test. In the end, the internal consistency analysis (reliability) of the questionnaire was performed through Cronbach´s (alpha). Results: The occurrence of hearing loss was significantly higher in the R and RQ groups (33,33% respectively). These same groups were those who considered their workplace noisy (over 50% of individuals chose response category repeatedly / always). The RQ group reported noise annoyance complaint in higher percentage (73.33%). Irritation, headache and fatigue were the symptoms of noise exposure, with greater significance in the C group (13,34%, 23,33% and 6,66%), R (16,67%, 6,67% e 13,33%), RQ (36,67%, 23,66% and 43,33%). In the four groups, the effects such as: hearing loss, stress, irritability, headache and fatigue were statistically significant in recognition of what noise may cause. With the exception of the C group, 70% of individuals of the other three groups believe that educational actions and exchange or maintenance of the equipment can improve the noise conditions in the workplace. Conclusion: Hearing loss was statistically significant in the R and the RQ groups. Most of the R and the RQ group think that their workplace is noisy, however only the RQ group complains of noise annoyance. It was evident that the most significant auditory and non-auditory complaints are from the R and the RQ groups. Internal consistency (reliability) of the questionnaire used in this study was excellent